Plexiform Unicystic Ameloblastoma: A Rare Variant of Ameloblastoma - Swapnil S. Deore; Rishikesh C. Dandekar; Aarti M. Mahajan; Rahul Patil; Nilima Prakash (Case Reports in Dentistry)
The term plexiform unicystic ameloblastoma refers to a pattern of epithelial proliferation that has been described in cystic cavity. Because of unilocular presentation, it is commonly misdiagnosed as an odontogenic cyst. However, they may often behave clinically as biologically aggressive tumors. These tumors show high incidence of cortical perforation, tooth resorption and a high rate of recurrence after simple enucleation. This paper aims to provide an insight into this biologically distinct entity. A literature review on the topic has been added along with a case report highlighting the approach of diagnosis and management of such ameloblastomas.